Karakteristik dan Faktor Risiko Pasien Kanker Kulit Di Rspal Dr. Ramelan Surabaya Periode Januari 2021-Desember 2023 - HIBATULLAH, HISYAM; OCTAVIANDA, YOHANA; RAHAYU, INDRI NGESTI; MUTIADESI, WAHYU PRASASTI (Hang Tuah Medical Journal, 2025)
Skin cancer is one of the most common types of cancer diagnosed worldwide. The incidence and mortality rates of skin cancer have also continued to increase in recent decades. In Indonesia, skin cancer is the cancer with the third highest incidence after uterine cancer and breast cancer. The purpose of this study was to determine the characteristics and risk factors of skin cancer patients at RSPAL dr. Ramelan Surabaya for the period January 2021-December 2023. Using a qualitative descriptive approach with variables in the form of secondary data that has been recorded in the medical records of skin cancer patients at RSPAL dr. Ramelan Surabaya for the period January 2021-December 2023. The data examined were the type of skin cancer, symptoms of skin cancer, location of skin cancer, patient age, and patient gender. The most characteristic type of skin cancer is Basal Cell Carcinoma in 51 cases. The most characteristic symptom of skin cancer was the formation of new moles/bumps in 67 cases. The characteristic of the location of skin cancer is mostly on the head in 69 cases. The age characteristics of cancer patients were most common in elderly patients at 56 cases. The sex characteristics of skin cancer patients were mostly female at 51 cases. The occupational characteristics of skin cancer patients were mostly indoor workers at 86 cases. Most cases were of the BCC type, with the most common symptom being the formation of new moles.